Diseño hidráulico y estructural de la bocatoma del proyecto de irrigación avisado – Valle “La Conquista” - Cunia Perez, Luis Ernesto (2005)
The following Engineering thesis is framed within the degree program according to the modality of formulation and the support of the thesis, which will lead to the author to obtain the professional title of civil engineer. For these aims it has been chosen to develop a subject of the area of titled hydraulics "Hydraulic and Structural Design of the Bocatoma of the Project of lrrigation "AvisadoValley La Conquista", which objective has been to study in depth the aspects of hydraulic design and structural of bocatoma over the river Avisado, in the valley la Conquista. The data considered in the analysis has been taken from Proyecto Especial Alto Mayo (PEAM), which brings up the use of the resources of the Avisado river, located in the smaller populated center Conquista, province of Moyobamba, region San Martín. Within this project it has been considered to irrigate approximately 2.200has; according to the feasibility study, made by the PEAM (1997). In this project an alternative of pickup in the Avisado river is considered to cover this demand. The development of the thesis appears through six chapters, as it follows: Chapter 1: The introduction to the thesis is indicated. lt indicates the location and position of project's zone, also the objectives and records to define the accomplishments of the thesis. Chapter 11: The analysis of the basic information available is made: geologic topography of the land, hydrological conditions, geological, etc. Chapter 111: The theoretical frame referring to the pick up of the structures appear, necessary information for the design of bocatomas, types of bocatomas, and the main parts of one bocatoma. Chapter IV: The hydraulic design of bocatoma appears, the design includes/understands the sizing of the derived dam, the pick up, the sysmtem of cleaning and walls of channeling. Chapter V: The structural design of bocatoma appears, the design includes/understands the reinforcing of the barrage, walls of channeling, slab of operation of the floodgate of cleaning and the pillar. Chapter VI: One indicates the conclusions and recommendations of the developed chapters.